Trading as Entertainment? - Dorn, Daniel; Sengmueller, Paul (Management Science, 2009)
Among 1,000 German brokerage clients for whom both survey responses and actual trading records are available, investors who report enjoying investing or gambling turn over their portfolio at twice the rate of their peers. Including entertainment attributes as additional explanatory variables in cross-sectional regressions of portfolio turnover on objective investor attributes more than doubles the fraction of the total variation of portfolio turnover that can be explained. The results are robust to controlling for gender and proxies for overconfidence constructed from survey responses. Nonpecuniary benefits of trading thus appear to offer a straightforward explanation of the “excessive trading puzzle.”